COMPARISON BETWEEN TRAGAL CARTILAGE WITH PERICHONDRIUM AND TEMPORALIS FASCIA GRAFT BY UNDERLAY ENDOSCOPIC TYMPANOPLASTY - Tahir, Muhammad; Abbass, Asim; Nawaz, Faiz Ul Hassan; Shabir, Syed Asad; Rafique, Atif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the results of tragal cartilage with perichondrium versus temporalis fascia graft in endoscopic tympanoplasty using underlay technique.Study Design: Comparative prospective study.Place and Duration of Study: Study conducted in Tertiary Care Hospital, Karachi, from Jul 2018 to Feb 2020.Methodology: Overall, 34 patients having permanent unilateral tympanic membrane perforations were included in this study, in whom underlay endoscopic tympanoplasty was performed. Group A patients underwent temporalis fascia graft while group B received a tragal cartilage with perichondrium graft. The success rate between groups was compared in respect of reduction in postoperative air-bone gap and healing of perforation.Results: The success rate of graft was 88% (30/34) in group A and 94% (32/34) in group B after 6 months follow-up, the difference was not found to be statistically significant (p=0.368). Hearing improvement in the form of closure of air bone gap in group A was from 24.52 ± 1.73 dB (decibel) to 13.56 ± 5.67s dB and in group B it was from 19.76 ± 3.47dB to 11.94 ± 3.9dB, the difference was not significant statistically (p=0.333).Conclusion: Keeping in view the results of our study, we conclude that both tragal cartilage with perichondrium and temporalis fascia graft are considered equally successful in endoscopic tympanoplasty.